Inter-Comparison of the Spatial Distribution of Methane in the Water Column From Seafloor Emissions at Two Sites in the Western Black Sea Using a Multi-Technique Approach - Grilli, Roberto; Birot, Dominique; Schumacher, Mia; Paris, Jean-Daniel; Blouzon, Camille; Donval, Jean Pierre; Guyader, Vivien; Leau, Helene; Giunta, Thomas; Delmotte, Marc; Radulescu, Vlad; Balan, Sorin; et al. (Frontiers in Earth Science, 2021)
Understanding the dynamics and fate of methane (CH4) release from oceanic seepages on margins and shelves into the water column, and quantifying the budget of its total discharge at different spatial and temporal scales, currently represents a major scientific undertaking. Previous works on the fate of methane escaping from the seafloor underlined the challenge in both, estimating its concentration distribution and identifying gradients. In April 2019, the Envri Methane Cruise has been conducted onboard the R/V Mare Nigrum in the Western Black Sea to investigate two shallow methane seep sites at ∼120 m and ∼55 m water depth. Dissolved CH4 measurements were conducted with two continuous in-situ sensors: a membrane inlet laser spectrometer (MILS) and a commercial methane sensor (METS) from Franatech GmbH. Additionally, discrete water samples were collected from CTD-Rosette deployment and standard laboratory methane analysis was performed by gas chromatography coupled with either purge-and-trap or headspace techniques. The resulting vertical profiles (from both in situ and discrete water sample measurements) of dissolved methane concentration follow an expected exponential dissolution function at both sites. At the deeper site, high dissolved methane concentrations are detected up to ∼45 m from the seabed, while at the sea surface dissolved methane was in equilibrium with the atmospheric concentration. At the shallower site, sea surface CH4 concentrations were four times higher than the expected equilibrium value. Our results seem to support that methane may be transferred from the sea to the atmosphere, depending on local water depths. In accordance with previous studies, the shallower the water, the more likely is a sea-to-atmosphere transport of methane. High spatial resolution surface data also support this hypothesis. Well localized methane enriched waters were found near the surface at both sites, but their locations appear to be decoupled with the ones of the seafloor seepages. This highlights the need of better understanding the processes responsible for the transport and transformation of the dissolved methane in the water column, especially in stratified water masses like in the Black Sea.